Phylogeny is a stronger predictor of activity than allometry in an African mammal community - Kasozi, H; Moll, R; Kityo, R; Montgomery, RA (Oxford University Press, 2021)
In promoting coexistence, sympatric species often partition shared resources along spatiotemporal domains. Similarly-sized and phylogenetically-close species, for instance, partition the times of day in which they are active to limit interference competition. Given that variation in species body mass has evolutionary underpinnings, species activity levels (time spent active in a 24-hour daily cycle) within animal communities might be structured by phylogeny. However, few studies have tested this hypothesis across animal communities, and none among medium to large mammals. We quantified the relative contributions of phylogeny and body mass in predicting activity levels in a community of 22 sympatric mammal species in Murchison Falls National Park, Uganda. We show that phylogeny is a stronger predictor of species activity levels than body mass. Our findings provide empirical evidence for the phylogenetic structuring of mammal activity in diverse communities. More broadly, our results suggest that evolutionary relationships mask allometry in predicting species traits in diverse animal communities.